Effects of an Intervention on Math Achievement for Students with Learning Disabilities - Kitchens, Vivian D.; Deris, Aaron R.; Simon, Marilyn K. (Journal of the American Academy of Special Education Professionals, 2016)
Students with learning disabilities score lower than other at-risk groups on state standardized assessment tests. Educators are searching for intervention strategies to improve math achievement for students with learning disabilities. The study examined the effects of a mathematics intervention known as Cover, Copy, and Compare for learning basic math computation skills. Fifteen students diagnosed with learning disabilities participated in this study using Curriculum Based Assessment probes to collect the data. There was a significant difference in math achievement from pre- to post-test scores for students with learning disabilities who participated in the Cover, Copy, and Compare treatment, t (14) = -15.09, p < 0.001. An analysis of covariance determined the efficacy of a Cover, Copy, and Compare intervention was not related to gender or ethnicity. One recommendation for future research is to conduct studies regarding Cover, Copy, and Compare instruction’s impact on student achievement for younger and older students with learning disabilities.